Visual Outcomes of Microkeratome-Assisted Anterior Lamellar Keratoplasty in Keratoconus: 5-Year Results - Ahmed Rashad Ashor; Mohamed-Sameh H. El-Agha; Mohamed Waleed Nagaty; Essam Abdel Ghaffar Darwish (Journal of Ophthalmology)
Purpose. To report 5-year results of microkeratome-assisted anterior lamellar keratoplasty (MK-ALK) in cases of keratoconus. Methods. Patients with advanced keratoconus and the thinnest corneal location 300 μ or more were recruited. A Carriazo–Barraquer microkeratome was used to remove a 200-μ cap from the recipient cornea, and to prepare a 300-μ anterior stromal graft from a donor cornea. A full-thickness crescentic incision was made in the posterior stromal recipient bed using a 6.5-mm suction trephine. The donor was sutured to the recipient bed using interrupted nylon sutures. The minimum follow-up was five years. Results. Twelve eyes of 12 patients were included. The mean age was 26 ± 8 years. None of the patients required conversion to penetrating keratoplasty. Mean logMAR uncorrected and best spectacle-corrected visual acuity, respectively, improved from 1.56 ± 0.24 and 1.18 ± 0.32 preoperatively, to 0.63 ± 0.38 and 0.18 ± 0.12, five years after surgery (P=0.001for both). There was also a statistically significant reduction of mean manifest spherical equivalent, refractive cylinder, and mean keratometry readings. Posterior stromal striations occurred in all patients immediately after surgery but resolved after a maximum of 3 months. At five-years, anterior segment optical coherence tomography revealed a clear interface in all cases and a mean graft thickness of 328 ± 27 μ. Conclusion. MK-ALK is a safe and effective procedure for advanced keratoconus. Where feasible, it may be the best choice for patients at high risk of poor outcomes with penetrating keratoplasty, such as young patients with atopic keratoconjunctivitis or Down’s syndrome.